If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2log(x + -1) = log(x + -1) Reorder the terms: 2glo(-1 + x) = log(x + -1) (-1 * 2glo + x * 2glo) = log(x + -1) (-2glo + 2glox) = log(x + -1) Reorder the terms: -2glo + 2glox = glo(-1 + x) -2glo + 2glox = (-1 * glo + x * glo) -2glo + 2glox = (-1glo + glox) Solving -2glo + 2glox = -1glo + glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'glo' to each side of the equation. -2glo + glo + 2glox = -1glo + glo + glox Combine like terms: -2glo + glo = -1glo -1glo + 2glox = -1glo + glo + glox Combine like terms: -1glo + glo = 0 -1glo + 2glox = 0 + glox -1glo + 2glox = glox Add '-1glox' to each side of the equation. -1glo + 2glox + -1glox = glox + -1glox Combine like terms: 2glox + -1glox = 1glox -1glo + 1glox = glox + -1glox Combine like terms: glox + -1glox = 0 -1glo + 1glox = 0 Factor out the Greatest Common Factor (GCF), 'glo'. glo(-1 + x) = 0Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1 + x)' equal to zero and attempt to solve: Simplifying -1 + x = 0 Solving -1 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0 + 1 x = 0 + 1 Combine like terms: 0 + 1 = 1 x = 1 Add '-1x' to each side of the equation. x + -1x = 1 + -1x Combine like terms: x + -1x = 0 0 = 1 + -1x Simplifying 0 = 1 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 50=3x-1-2x+1 | | 50=3x-1+2x+1 | | 4x+5-7x=-15 | | 50=3x-12x+1 | | 10x^2+3x+9=13 | | X^2-6x-11=-4 | | x*6+86=x*10-6 | | f(x)=9xsquared+5x+1 | | 2[x+8]=-4[5x-2]+8x | | 2x-7+4x+15=56 | | (4x-7)+(-12-8x)= | | 3+25x=20x+12 | | 15-4t=4 | | 3+25x=20x-12 | | e^4x=10 | | 2z(z)+20z=0 | | 3+25x=2-0x+12 | | 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 |